ETNOMATHEMATHICS IN JAVANESE RIBBON: THE MEANING OF EVERY LOST OBJECT - Rahmah, Latifah Fitriana; Untarti, Reni; Gunawan, Gunawan (Yayasan Education and Social Center, 2024)
The use of Primbon in determining the meaning of lost objects reflects how local traditions and beliefs still influence the daily practices of Javanese society. This study aims to dig deeper into how Ethnomathematics is used in Javanese culture to give meaning to everyday phenomena, such as when losing objects. The research method used in this study is the descriptive qualitative method. Data were collected through observation, interviews, and literature study. The observation was conducted by observing the Javanese Primbon calculation activities in Panican Village, Kemangkon Subdistrict, Purbalingga Regency, Central Java Province, Indonesia. The interview used in this research is semi-structured with the resource person, Mr. SH. The data source in this research uses secondary data obtained by conducting a literature study of the versatile Javanese primbon book owned by R. Gunasasmita. The results of this study indicate the existence of Ethnomathematics in giving meaning to the calculation of Primbon in Javanese culture, which uses the mathematical concept of modulo 3 and 4 to determine the meaning of lost objects, such as who the thief is, gender, skin colour, and whether the lost object will be found again